Leveraging sport heritage to promote tourism destinations: the case of the Tour of Flanders Cyclo event. Issue 3 (1st October 2016) - Derom, Inge; Ramshaw, Gregory
ABSTRACT: The conceptual framework of event leverage has been applied to cases of event sport tourism, but it has been under-examined in cases of heritage-based active sport tourism. Using the framework of event leverage, the purpose of this paper is to explore the strategic opportunities for tourism destination development associated with hosting heritage-based active sport tourism events. Quantitative and qualitative survey data were collected from participants ( N = 1091) at the 2013 edition of the Tour of Flanders Cyclo event. This annual active sport tourism event has gained world-wide popularity through explicit associations with Flanders' cycling heritage. The findings reveal significant differences between national and international event participants in terms of their socio-demographic profiles, cycling behaviours, and event motivations. Active sport tourists who travelled internationally to take part in the event were more committed to experiencing and pursuing the event's heritage, as active participants as well as passive spectators. While sport tourism events are commonly identified as the key resource in the event leveraging literature, this paper highlights the leveraging potential of other event and destination-related resources, including event heritage, route, and atmosphere. The findings contribute to the conceptual framing of event leverage by identifying active sport heritage as an important resource to promote participation among sport tourists. This study suggests a broader conceptualisation of sport heritage as an active and embodied process. Event stakeholders are advised to create temporary and permanent transformations that can enhance the connection between the facets of the event and the context of the host to attract domestic and international participants all year round.